Dietary supplementation of Withania somnifera and Asparagus racemosus enhances growth performance coupled with transcriptional modulation of growth and immune responsive genes in fish, Channa punctatus - Sunil P. Trivedi; Shikha Dwivedi; Shefalee Singh; Adeel Ahmad Khan; Manoj Kumar; Indrani Dubey; Abha Trivedi; Vivek Kumar; Kamlesh K. Yadav (Aquaculture and Fisheries, 2025)
The growth amelioration potential of two herbal feed supplements, Withania somnifera and Asparagus racemosus, individually and in combination, was evaluated up to 60 days of feeding trial in a teleost, Channa punctatus. 15 days laboratory acclimatized fish (14 ± 1) g; (11 ± 1) cm were randomly distributed in 10 groups- C (control), S1, S2, S3, A1, A2, A3, AS1, AS2, and AS3, based on the composition of the dietary supplements. Each group had 10 specimens (n = 10), and the experiment was performed in triplicate. Elevated final body weight (FBW) was observed in all groups except S1 after 60 days, and weight gain percentage (WG %) showed a significant increase in all groups except S1 after both 30 and 60 days of the sampling periods with a significance level of P < 0.05. In contrast, the feed conversion ratio (FCR) significantly (P < 0.05) decreased in all experimental groups, except S1, as compared to the control, after 60 days of sampling duration. The hepatosomatic index (HSI %) significantly (P < 0.05) increased in groups - S3, A2, A3, AS1, AS2, and AS3; while the viscerosomatic index (VSI %) also significantly (P < 0.05) enhanced in groups - A3, AS1, AS2, and AS3 as compared to C. Significant (P < 0.05) elevations in activities of both trypsin and chymotrypsin, after both the sampling durations were recorded; the maximum being in AS3 as 3.47 and 2.06-fold, respectively, after 60 days, suggests greater protein digestibility. The qRT-PCR analysis displays an up-regulation of growth-related genes-gh, igf-1, and igf-2a, both in the liver and muscle tissues. Also, gh showed greater expression at transcriptional levels in liver tissues (4.86)-fold than muscle tissues (4.43)-fold in AS3; whereas igf-1 and igf-2a were significantly (P < 0.05) upregulated in the muscles of AS2 and AS3 as compared to C. Further, significantly (P < 0.05) increased expression of the transforming growth factor-β (tgf-β) in liver tissues was recorded in groups- AS1, AS2, and AS3, as compared to C, suggesting the immunoprotective role of combined dietary supplements. The study envisages that 3% dietary supplementation with both herbs (AS3) sufficiently influences the activities of digestive enzymes, growth indices, and mRNA levels of growth-related and immunoprotective genes in the fish. The study thus finds ample scope in aquaculture.